Employment After Stroke: Report of a State of the Science Symposium. Issue 1 (March 2014) - Roth, Elliot J.; Lovell, Linda
Abstract : For many stroke survivors, returning to work becomes an important emotional and functional milestone in signaling recovery. It can also provide needed financial support and reduce the burden placed on society in the form of government assistance. The complex nature of the return-to-work process involves many factors that may support or interfere with reintegration into the workforce. For the purpose of examining this important topic more closely, the Rehabilitation Research & Training Center on Enhancing the Functional and Employment Outcomes of Individuals Who Experience a Stroke held a State of the Science Symposium on employment after stroke on November 7, 2011, which was supported by the US Department of Education, National Institute on Disability and Rehabilitation Research. Six questions were posed to the symposium members, who developed research and policy recommendations to address the issues facing stroke survivors seeking to return to work.